(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article analyzes the process of historical and cultural formation of national costumes, their inextricable connection with the life, customs, and traditions of the people. It also highlights the changes that have occurred in national costumes in different periods, their regional characteristics, and their artistic and aesthetic essence. The spiritual and symbolic meaning of national costumes expressed in terms of color, ornamentation, fabric, and shape is revealed, and their significance today and their place in modern design are examined. The article also pays special attention to the issues of preserving national heritage and passing it on to the younger generation.